Humour in the classroom - Pereira, Helen (Universiti Teknologi MARA, Sarawak, 2004)
Humour and laughter are areas that have not been closely studied. Their role in education and medicine has been briefly examined as far back as Wells (1974) to as recently as Provine (Dec. 2000) in, "The Science of Laughter", Psychology Today. Loomax and Moosavi (1998) in an article on the use of humour in a university statistics class point out that anecdotal evidence in past studies consistently suggests that humour is an extremely effective tool in education. These same studies suggest that the use of humour in the classroom reduces tension, improves classroom climate, increases enjoyment, increases student-teacher rapport and even facilitates learning.